Sustainable city – flexible or durable? Socio-economics aspects of urban patterns - Sadowy, Katarzyna (Economy Today: An Interdisciplinary Approach to Contemporary Economic Challenges, 2016)
This paper’s goal is to introduce an interdisciplinary assessment of urban patterns as a factor of socio-economic development, presenting selected examples of how different urban patterns (compactness, complexity, decentralisation and porosity) influence family economics, risk management for city dwellers and entrepreneurs, labour market and social inclusion or inequality. Urban patterns and socio-economic aspects of urban life are closely linked in a complex and manifold way. The main topic of the paper will be the assessment in what way durability or flexibility of a built environment influences urban sustainable development.It is not possible to identify one spatial pattern that in the best way meets the need to adapt to new challenges and threats. However, case studies can point to certain features of cities, especially their diversity, as being the most important for their proper functioning.